2006
DOI: 10.1103/physrevb.73.045208
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofEδand triplet point defects in oxygen-deficient amorphous silicon dioxide

Abstract: We report an experimental study by electron paramagnetic resonance (EPR) of γ ray irradiation induced point defects in oxygen deficient amorphous SiO 2 materials. We have found that three intrinsic (E' γ , E' δ and triplet) and one extrinsic ([AlO 4 ] 0 ) paramagnetic centers are induced. All the paramagnetic defects but E' γ center are found to reach a concentration limit value for doses above to the hyperfine structure of the E' δ center, originating from the interaction of the unpaired electron with a nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Furthermore, we have found that the concentration of twofold coordinated Si defect in the KUVI sample before thermal treatment is about one order of magnitude lower than the concentration of the thermally induced E' α centers, indicating that the twofold coordinated Si does not act as precursor defect for the E' α center. Consequently, we suggest that the E' α center arises from an oxygen vacancy by trapping a hole in a process similar to that proposed for the E' γ [8,9]. Since we exclude that an isothermal treatment at T=630 K could be able to move an oxygen atom out from its regular site of a-SiO 2 , as suggested in the model proposed by Griscom [3] for the E' α , we suppose that oxygen vacancies present in the material before thermal treatment at T=630 K are involved.…”
supporting
confidence: 60%
See 4 more Smart Citations
“…Furthermore, we have found that the concentration of twofold coordinated Si defect in the KUVI sample before thermal treatment is about one order of magnitude lower than the concentration of the thermally induced E' α centers, indicating that the twofold coordinated Si does not act as precursor defect for the E' α center. Consequently, we suggest that the E' α center arises from an oxygen vacancy by trapping a hole in a process similar to that proposed for the E' γ [8,9]. Since we exclude that an isothermal treatment at T=630 K could be able to move an oxygen atom out from its regular site of a-SiO 2 , as suggested in the model proposed by Griscom [3] for the E' α , we suppose that oxygen vacancies present in the material before thermal treatment at T=630 K are involved.…”
supporting
confidence: 60%
“…After irradiation of the materials considered, E' δ and E' γ centers are induced, but virtually no EPR signal due to E' α centers is detected [7][8][9]. As discussed extensively in our previous works [7][8][9], upon thermal treatment at T>500 K the EPR signal of E' γ and E' δ centers increases as a consequence of a hole transfer process form the [AlO 4 ] 0 centers to the sites precursors of the E' centers.…”
mentioning
confidence: 62%
See 3 more Smart Citations